Contribution of Egr1/zif268 to Activity-Dependent Arc/Arg3.1 Transcription in the Dentate Gyrus and Area CA1 of the Hippocampus - Penke, Zsuzsa; Chagneau, Carine; Laroche, Serge (Frontiers in Behavioral Neuroscience, 2011)
Egr1, a member of the Egr family of transcription factors, and Arc are immediate early genes known to play major roles in synaptic plasticity and memory. Despite evidence that Egr family members can control Arc transcriptional regulation, demonstration of a selective role of Egr1 alone is lacking. We investigated the extent to which activity-dependent Arc expression is dependent on Egr1 by analyzing Arc mRNA expression using fluorescence in situ hybridization in the dorsal dentate gyrus and CA1 of wild-type and Egr1 knockout mice. Following electroconvulsive shock, we found biphasic expression of Arc in area CA1 in mice, consisting in a rapid (30 min) and transient wave followed by a second late phase of expression (8h), and a single but prolonged wave of expression in the dentate gyrus. Egr1 deficiency abolished the latest, but not the early wave of Arc expression in CA1, and curtailed that of the dentate gyrus. Since the early wave of Arc expression was not affected in Egr1 mutant mice, we next analysed behaviorally-induced Arc expression patterns as an index of neural ensemble activation in the dentate gyrus and area CA1 of wild-type and Egr1 mutant mice. Spatial exploration of novel or familiar environments induced in mice a single early and transient wave of Arc expression in the dentate gyrus and area CA1, which were not affected in Egr1 mutant mice. Analyses of Arc-expressing cells revealed that exploration recruits similar size dentate gyrus and CA1 neural ensembles in wild-type and Egr1 knockout mice. These findings suggest that hippocampal neural ensembles are normally activated immediately following spatial exploration in Egr1 knockout mice, indicating normal hippocampal encoding of information. They also provide evidence that in condition of strong activation Egr1 alone can control late phases of activity-dependent Arc transcription in the dentate gyrus and area CA1 of the hippocampus.